EXAMINING THE INFLUENCE OF PROJECT SUSTAINABILITY PRACTICES ON PROJECT SUCCESS - Aruna Sunassee; Chandra Reka Ramachandiran; Vijayaraj Vijayasingam (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Many projects fail because resources are not managed efficiently. As a result, Project Managers have become concerned with sustainable project management and its influence on project success. However, there is a gap in literature regarding the relationship of these two frameworks that is sustainable project management and project success. In fact, the term sustainability is among the toughest challenges that mankind will ever have to face since its definition has evolved to encompass more than just sustainable environmental development but social and economic sustainability as well. Thus, the versatility of the term sustainability has caused more awareness and relevance to the all of society. Consequently, many organisations are presently integrating this popular approach into their business practices, which alternatively influences the outcomes of projects. As such, the aim of this research is to contribute to the knowledge area by assessing the factors that influence sustainable project management on project success and therefore integrating project management practices to project success.